Carbon dioxide sequestration of fly ash alkaline based mortars with recycled aggregates and different sodium hydroxide concentrations: Properties, durability, carbon footprint, and cost analysis - Mastali, Mohammad (2018)
This chapter discloses results of an investigation concerning carbon dioxide sequestration on fly ash/waste glass alkaline-based mortars with recycled aggregates and different sodium hydroxide concentrations. Properties, durability, carbon footprint, and cost analysis were studied on it. Mixtures using a sodium hydroxide concentration of 8M and the additive calcium hydroxide show the best performance and the lowest carbon footprint. Simulations using a carbon tax of 0.0347 Euro/kg show no influence on the cost of the mixtures while the use of the carbon tax of 0.206 Euro/kg show an increase in the cost-efficiency of mixtures, even those using a sodium hydroxide concentration of 8M and additive calcium hydroxide.